(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article is devoted to the issues of second language acquisition and the analysis of adult learners’ errors, which in Kazakh linguistics is considered from a different angle in recent years and has gained practical importance. The study provides a review of the research conducted by foreign scholars within the framework of applied linguistics on second language acquisition and error analysis, highlighting their definitions, theoretical approaches, and conclusions. The research employs methods of continuous sampling, classification, systematization, descriptive analysis, and comparative analysis. Opinions of foreign scholars on second language acquisition and the errors of adult learners are compared and categorized. Particular attention is given to the phenomenon of interlanguage: the processes influencing its emergence and the stages of second language acquisition are presented in a schematic form. Theoretical aspects of second language acquisition are comprehensively examined. As practical material, the study analyzes errors made by Turkmen students studying at Al-Farabi Kazakh National University, for whom Kazakh functions as a second language. The exclusive focus on foreign scholarly works indicates that the issue of second language acquisition in domestic research, particularly in Kazakh linguistics, remains at an early stage of development. Keywords: second language acquisition, error analysis, adult learners, applied linguistics.